An analytical study on the resident's satisfaction of rural rejuvenation plan in Taiwan: grey relational analysis of grey system theory. (2016) - Huang, Chih-Cheng; Hsieh, Ming-Yuan
This research employed the grey relational analysis of the grey theory to comprehensively analyse the community resident's satisfaction of the rural rejuvenation plans by the measurements of the large-scale surveyed questionnaires collected from the random community residents of the entire rural villages in Taiwan. After a series of measured results, there are four contributive findings: (1) the interviewed community residents feel more satisfaction in identification, partnership and commitment between the representative organisation of rural village and community residents in execution of rural rejuvenation plans; (2) they think that rural rejuvenation plans can activate the production activities and improve the innovation of production activities of rural village; (3) they deem that rural rejuvenation plans can improve the cultural conservation and facilities of rural village through the construction of the public hardware construction of cultural conservation and facilities of rural village and (4) they consider that rural rejuvenation plans can really strengthen the ecological protection of rural village because the complete modes of life and relation to their environment can be checked through the execution of these plans.